Perancangan Virtual Local Area Network Berbasis VTP Dan Inter-Vlan Routing - Prasojo Herdy Sutanto (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Abstract – With the increasing use of computers in Tirta Regional Water Company located in Pakuan Bogor. Communication between computers that are currently using a traditional LAN network. The need to collect data and information in its management requires appropriate computer network technology and can provide maximum results both in terms of computer management efficiency that can be arranged based on a particular group of work divisions and security enhancements that are needed by this Company.So the solution is to use VLAN network technology (Virtual Local Area Network), which can give better result in compare Local Area Network (LAN). With the implementation of VLAN technology is expected to provide convenience and flexibility in a variety of information systems services are always increasing and in the implementation always requires communication between computers in the network.Improved performance of government that is more advanced and expected to be more developed, the need for information management in every field both managed by the government and public facilities make an excuse for the development of computer network in the form of VLAN network. Viewing the network topology of the building, the area of coverage and the distance of a complex connection to be the right reason also to apply VLAN network technology. As for several reasons using the network which is the solution of the problem of data and information management needs, has a value of cost efficiency and high flexibility in maintenance and network construction.